The Chemical Quality of Maggot Flour Uses Sangrai Method Processing - Lestariningsih Lestariningsih; Tika Fitria Wulan Afrilia; Muhammad Muhsin; Muhammad Yusuf Yasin; Mas'ud Zakqi Hupron (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
The purpose of this study is to determine the differences of chemical quality of fresh maggot flour processed by using sangrai method. Currently maggot flour is popular among breeders because it contents high enough protein and has potential as a substitution of fish meal which has been imported at in very costly price. This research is conducted experimental methods on April 2021. The research consists of making maggot flour and continued to chemical analysis (proximate). Maggot which is processed into flour is obtained from maggot breeders in Blitar district. Maggot is processed by using sangrai method is carried out in Dayu Village, Nglegok District, Blitar Regency. Proximate analysis is carried out at the Nutrition and Animal Feed Laboratory of the Fisheries and Livestock Service Office of Blitar Regency. The sangrai method processing produces lower moisture content (5.69%) so that it is predicted to have a better shelf life. The rough protein is 28.73%, the rough fat content is 15.79%, and the rough fiber content is 10.60%. The results are considering higher. The maggot processed by using sangrai method can be applied, but it needs to be accompanied by further researches to reduce the higher rough fat and rough fiber content, one of them is fermentation.